Effects of flywheel resistance training on muscle function and sport-specific performance in collegiate club water polo players - Xu, J.; Thompson, B. J.; Spencer, S. B.; Studenka, B. E.; Bressel, E. (Research Quarterly for Exercise and Sport, 2023)
Purpose: This study investigated the effects of flywheel squat training on lower body muscle function adaptations and sport-specific performance in collegiate club water polo players. Methods: Thirteen collegiate club water polo athletes (5 women, 8 men) performed flywheel squat training for 4 weeks. Isokinetic knee extension (KE) peak power (PP) and peak torque (PT), flywheel squat peak power (FPP) and mean power (FMP), countermovement jump (CMJ), in-water jump height (WJH) and foot speed were assessed at baseline (Pre1), 4 weeks (Pre2), and 8 weeks (Post) with the first 4 week block being a control period and the second 4 week block being the experimental training. Throughout the training period muscle soreness was assessed using a VAS scale, and FPP and FMP were assessed during every other session. Results: Isokinetic KE PP and PT increased from Pre1 to Post, and FPP and FMP increased between Pre1 and Post, and Pre2 and Post. CMJ and foot speed were unchanged. WJH displayed a change between Pre1 and Post. FPP increased 19% from session 2 to 4 and FMP increased 27% from session 2 to 6, and each remained elevated through session 8. Conclusion: 4 weeks of flywheel squat training in collegiate club water polo players elicited large gains (47-52%) in flywheel-specific squat power, but did not influence sport-specific performance measures including CMJ, WJH, and foot speed. Water-based exercises and stretch-shortening cycle movements (plyometrics) in combination with effective resistance training programs, which may include flywheel-based training, are likely needed for marked sport skill improvements.